Thoughts on the promotion of modern and contemporary ancient poetry art songs from “Marginalization” to “Mainstream” (Journal of Namibian Studies : History Politics Culture, 2023)
with the development of the times and social changes, the creation of modern and contemporary ancient poetry art songs is increasingly difficult, artistic expression of the rich, difficult to enhance the creation of traditional culture and other factors have a huge impact on its deepening. In this case, the modern and contemporary ancient poetry art songs increasingly prominent phenomenon of marginalization, and the causes of its marginalization is also worth in-depth study. This paper aims to analyze the causes of the marginalization of the art songs of modern and contemporary ancient poetry, and put forward the corresponding countermeasures and suggestions to promote the diversification of their art forms and the improvement of their creative quality.